2022
DOI: 10.3389/fmicb.2022.807057
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Root Microbial Community Composition Significantly Associated With Root-Knot Nematode Infections: Dynamic Changes in Microbiota and Growth Stage

Abstract: The root-knot nematode (RKN) is an important pathogen that affects the growth of many crops. Exploring the interaction of biocontrol bacteria-pathogens-host root microbes is the theoretical basis for improving colonization and controlling the effect of biocontrol bacteria in the rhizosphere. Therefore, 16S and 18S rRNA sequencing technology was used to explore the microbial composition and diversity of tobacco roots (rhizosphere and endophytic) at different growth stages in typical tobacco RKN-infected areas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The Micropepsaceae has been found to be an indicator taxon associated with specific plant species or site conditions in other studies (D. Wu et al 2023;Gschwend et al 2022). For studies that compared different environmental manipulations, the family was associated with early phases of restoration (grasslands; (Barber et al 2023)), early responses to agricultural planting (tobacco; (Cao et al 2022)), and response to cold treatments of plants (lettuce; (Persyn et al 2022)), all conditions in which a system had been perturbed recently. In one study, the presence of Micropepsaceae was also associated with reduced suppression of pathogens .…”
Section: Discussionmentioning
confidence: 90%
“…The Micropepsaceae has been found to be an indicator taxon associated with specific plant species or site conditions in other studies (D. Wu et al 2023;Gschwend et al 2022). For studies that compared different environmental manipulations, the family was associated with early phases of restoration (grasslands; (Barber et al 2023)), early responses to agricultural planting (tobacco; (Cao et al 2022)), and response to cold treatments of plants (lettuce; (Persyn et al 2022)), all conditions in which a system had been perturbed recently. In one study, the presence of Micropepsaceae was also associated with reduced suppression of pathogens .…”
Section: Discussionmentioning
confidence: 90%
“…However, the members of Phaeosphaeriaceae, particularly Setophoma spp. have been reported as an endophyte of Panax ginseng and several other plants 50 52 .…”
Section: Discussionmentioning
confidence: 99%
“…RKNs significantly affect the rhizosphere soil and root-endophytic microbial communities of the host plant ( Tian et al, 2015 ; Wolfgang et al, 2019 ; Zhou et al, 2019 ; Cao et al, 2022 ). Meanwhile, the microorganisms would produce secondary metabolites to affect the RKNs infection.…”
Section: Discussionmentioning
confidence: 99%
“…RKN infection of plants leads to physiological changes in the host and affects the composition of root exudates ( Tian et al, 2015 ). Some of these root exudates can directly antagonize disease and insect pests, while others can collect and select microbial flora conducive to plant growth under the action of microbial chemotaxis ( Bücking et al, 2008 ; Cao et al, 2022 ). It is suggested that the different regulations of the abundance of Bacillus , Flavobacterium , and Pseudomonas resulted from the interaction among nematodes, fungi, and plants in rhizosphere soils.…”
Section: Discussionmentioning
confidence: 99%